PROSTHETIC LIMB USER EXPERIENCES WITH CROSSOVER FEET: A FOCUS GROUP STUDY TO EXPLORE OUTCOMES THAT MATTER - Cody L. McDonald; Sarah M. Cheever; Sara J. Morgan; Brian J. Hafner (Canadian Prosthetics & Orthotics Journal, 2018)
INTRODUCTION